CAMBRIDGE CRYSTALLOGRAPHIC DATABASE ANALYSIS OF SOME MEDICINALLY IMPORTANT HALOGENATED AMINOPYRIDINES - Ruchika Sharma1, Saminathan Murugavel2 and Rajni Kant3 (university of eloued جامعة الوادي, 2024)
A database comparison of the crystal structure of some halogenated aminopyridine derivatives has been performed for their structural optimization and quantum chemical analysis. The investigation explores the optimum structural geometry of the identified molecules, including the frontier orbital energy gap, Mulliken atomic charge distribution and molecular electrostatic potential (MEP). The two-dimensional fingerprint plots and Hirshfeld surface analysis reveals diverse intermolecular interactions existing between the molecules. The void volume percentage has been computed to infer about the physical strength of these molecules. Molecular docking has been performed to reveal that all the molecules could be potential candidates for an efficient potent inhibitor for MET receptor
Keywords: X-ray structure; Optimization; HOMO-LUMO; Hirshfeld surfaces; Molecular docking.